مشكلة الاراضي بين عشيرتي ال حاتم والمناع في لواء المنتفك حتى عام 1958 - الهلالي م.د سلمان رشيد محمد (Thi Qar Arts Journal, 2021)
The research is a review of the land problem of the Hatim clan (one of the Bani Reckab clans) in the Liwa al-Muntafak and the historical development of the roots of the land problem in Iraq in general and al-Mutafak in particular, and the role of the governor over Iraq, Medhat Pasha (1869-1872) in establishing the pattern of feudalism in the country, and the Saadoun monopolizing possession of that Agricultural lands and giving them to those close to them, the most important of whom is manna. And the problems that occurred as a result of that and the uprisings by the Al Hatim clan in the years (1927, 1936, 1941) against Manna, the Iraqi government’s position on those uprisings and the role of MP Zamil Al-Manaa in instigating and thwarting them .